Thinking about statutes: interpretation, interaction, improvement - Burrows, A. S. (Cambridge University Press, 2018)
We are in the age of statutes; and it is indisputable that statutes are swallowing up the common law. Yet the study of statutes as a coherent whole is rare. In these three lectures, given as the 2017 Hamlyn Lecture series, Professor Andrew Burrows takes on the challenge of thinking seriously and at a practical level about statutes in English law. In his characteristically lively and punchy style, he examines three central aspects which he labels interpretation, interaction and improvement. So how are statutes interpreted? Is statutory interpretation best understood as seeking to effect the intention of Parliament or is that an unhelpful fiction? Can the common law be developed by analogy to statutes? Do the judges have too much power in developing the common law and in interpreting statutes? How can our statutes be improved? These and many other questions are explored and answered in this accessible and thought-provoking analysis
OCLC: 1048404559